2005
DOI: 10.1021/jp044535g
|View full text |Cite
|
Sign up to set email alerts
|

Excess Proton Solvation and Delocalization in a Hydrophilic Pocket of the Proton Conducting Polymer Membrane Nafion

Abstract: Solvation properties of the hydrated excess proton are studied in a hydrophilic pocket of Nafion 117 through a series of molecular dynamics simulations. The multistate empirical valence bond (MS-EVB) methodology, which enables the delocalization of the excess proton through the Grotthuss hopping mechanism, was employed for one of the excess protons in the simulation cell. Simulations were performed such that "classical" nondissociable hydronium cations and a single excess proton treated with the MS-EVB methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 21 publications
7
131
1
Order By: Relevance
“…15) dependence of the mobility and showed that the dominant diffusion of the protons occurs in regions separated from the sulfonate groups. This latter result compares favourably with the earlier discussed EVB simulations of Petersen et al 51 where at l = 9 they observed maxima in the sulfonate-oxygen-hydroniumoxygen radial distribution function at 2.6 Å (contact ion pair) and 4.4 Å (solvent-separated ion pair).…”
Section: This Journal Is C the Owner Societies 2007supporting
confidence: 90%
“…15) dependence of the mobility and showed that the dominant diffusion of the protons occurs in regions separated from the sulfonate groups. This latter result compares favourably with the earlier discussed EVB simulations of Petersen et al 51 where at l = 9 they observed maxima in the sulfonate-oxygen-hydroniumoxygen radial distribution function at 2.6 Å (contact ion pair) and 4.4 Å (solvent-separated ion pair).…”
Section: This Journal Is C the Owner Societies 2007supporting
confidence: 90%
“…20,59 As discussed in the Introduction, many studies were performed to describe the hopping mechanism and obtained reasonable results. [26][27][28][29][30] However, because this study mainly focuses on the PEM morphology under hydrated conditions, such a model using excess protons is not applied. As a result, the diffusivity of Nafion in simulations is lower than that from the experimental results (about 7 × 10 -6 cm 2 s -1 at 303.15 K 60 ) due to the absence of the additional driving force of the hopping mechanism.…”
Section: Phase Separation and Water Channel Morphologymentioning
confidence: 99%
“…[1][2][3][4][5] Alternatively, perturbative quantum methods have also been successfully applied to many systems, but they are intrinsically limited to a single reference geometry. [6][7][8][9][10][11] High dimensional systems, such as peptides, are instead usually simulated through ad-hoc scaled harmonic approaches or by means of classical mechanics, either using force fields [12][13][14] or employing ab initio molecular dynamics (AIMD) [15][16][17][18][19][20][21] approaches in which the nuclear forces are calculated using electronic structure codes. In classical simulations the curse of dimensionality is significantly tamed with respect to quantum mechanical counterparts.…”
Section: Introductionmentioning
confidence: 99%